1986
DOI: 10.1007/bf01785710
|View full text |Cite
|
Sign up to set email alerts
|

Myoadenylate deaminase deficiency: Successful symptomatic therapy by high dose oral administration of ribose

Abstract: A 55 years old patient suffering from exercise-induced muscle pain and stiffness due to primary myoadenylate deaminase deficiency has been successfully treated with D-ribose since 1984: single doses of 4 grams administered at the beginning of exercise prevented the symptoms completely; on continuation of exercise this dose had to be repeated all 10-30 min. Total doses of 50-60 g per day were tolerated without side-effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
33
1

Year Published

1991
1991
2011
2011

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(37 citation statements)
references
References 49 publications
3
33
1
Order By: Relevance
“…7, 8], That may be attributed to reduced stimulation of glycogenolysis and glycolysis by lack of am monia and IMP [9], The increase of plasma lactate concentrations during muscular exer cise after oral administration of ribose in 2 of 3 AMPD-deficient patients found in our experiments suggests that the beneficial cf-feet of ribose may be due to an additional energy source [2], This hypothesis is in part contradicted by the fact that plasma lactate concentrations of the patient with the best therapeutic effect of ribose (patient 1) re mained unchanged after oral administration of ribose, whereas plasma lactate concentra tions of the patient with no apparent thera peutic effect at all (patient 2) were most increased after oral administration of ri bose.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…7, 8], That may be attributed to reduced stimulation of glycogenolysis and glycolysis by lack of am monia and IMP [9], The increase of plasma lactate concentrations during muscular exer cise after oral administration of ribose in 2 of 3 AMPD-deficient patients found in our experiments suggests that the beneficial cf-feet of ribose may be due to an additional energy source [2], This hypothesis is in part contradicted by the fact that plasma lactate concentrations of the patient with the best therapeutic effect of ribose (patient 1) re mained unchanged after oral administration of ribose, whereas plasma lactate concentra tions of the patient with no apparent thera peutic effect at all (patient 2) were most increased after oral administration of ri bose.…”
Section: Discussionmentioning
confidence: 90%
“…Zöllner et al [2] first demonstrated that the oral administration of high doses of ri bose may be a successful therapy in AMPD deficiency. Gross et al [5] from the same laboratory found that orally administered ri bose is absorbed intestinally by 88-100% in both healthy subjects and AMPD-deficient patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations